PENGARUH PELAYANAN PETUGAS CLEANING SERVICE TERHADAP KEPUASAN PENGGUNA JASA DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Farhan Irfani; Eny Sri Haryati (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Abstract. Cleaning service officers must provide satisfaction and comfort for service users because service is very influential on the image and quality at Yogyakarta International Airport. This study aims to determine whether the service of cleaning service officers affects service user satisfaction at Yogyakarta International Airport. This research is a quantitative study using purposive sampling, with a sample size of 100 passengers measured using the Slovin formula. The data collection process using questionnaires, documentation and data analysis used is simple linear regression, T test and coefficient of determination then processing the data using the SPSS application. The results of this study indicate that the cleaning service officer service variable has a significant effect on service user satisfaction at Yogyakarta International Airport with a sig value (0.000 <0.05) and has a T count (16.366) > T table (1.660). Then the results of the coefficient of determination obtained 0.732, this means that the influence of cleaning service officers on service user satisfaction is 73.2%.